Editor's Choice – Systematic Review and Meta-Analysis of Wound Adjuncts for the Prevention of Groin Wound Surgical Site Infection in Arterial Surgery. (April 2021) - Gwilym, Brenig L.; Dovell, George; Dattani, Nikesh; Ambler, Graeme K.; Shalhoub, Joseph; Forsythe, Rachael O.; Benson, Ruth A.; Nandhra, Sandip; Preece, Ryan; Onida, Sarah; Hitchman, Louise; Coughlin, Patrick; et al.
Abstract : Objective: Groin incision surgical site infections (SSIs) following arterial surgery are common and are a source of considerable morbidity. This review evaluates interventions and adjuncts delivered immediately before, during, or after skin closure, to prevent SSIs in patients undergoing arterial interventions involving a groin incision. Data sources: MEDLINE, EMBASE, and CENTRAL databases were searched. Review methods: This review was undertaken according to established international reporting guidelines and was registered prospectively with the International prospective register of systematic reviews (CRD42020185170). The MEDLINE, EMBASE, and CENTRAL databases were searched using pre-defined search terms without date restriction. Randomised controlled trials (RCTs) and observational studies recruiting patients with non-infected groin incisions for arterial exposure were included; SSI rates and other outcomes were captured. Interventions reported in two or more studies were subjected to meta-analysis. Results: The search identified 1 532 articles. Seventeen RCTs and seven observational studies, reporting on 3 747 patients undergoing 4 130 groin incisions were included. A total of seven interventions and nine outcomes were reported upon. Prophylactic closed incision negative pressure wound therapy (ciNPWT) reduced groin SSIs compared with standard dressings (odds ratio [OR] 0.34, 95% CI 0.23 – 0.51; p < .001, GRADE strength of evidence: moderate). Local antibiotics did not reduce groin SSIs (OR 0.60 95% CI 0.30 – 1.21 p = .15, GRADE strength: low). Subcuticular sutures ( vs . transdermal sutures or clips) reduced groin SSI rates (OR 0.33, 95% CI 0.17 – 0.65, p = .001, GRADE strength: low). Wound drains, platelet rich plasma, fibrin glue, and silver alginate dressings did not show any significant effect on SSI rates. Conclusion: There is evidence that ciNPWT and subcuticular sutures reduce groin SSI in patients undergoing arterial vascular interventions involving a groin incision. Local antibiotics did not reduce groin wound SSI, although the strength of this evidence is lower. No other interventions demonstrated a significant effect.